Analysis of Environment and Control Activities Over Inventory Management of Medicines and Supplies at Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) of North Sulawesi - Lester, Casey; Wokas, Heince RN; Datu, Christian (ACCOUNTABILITY, 2024)
This research aims to determine the internal control system for inventory administration based on frameworks one and three of COSO, namely the environment and control activities at Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) of North Sulawesi. The research method used in this research is primary data using observation, interview and documentation data collection techniques. The results of this research show that the internal control system includes two COSO components, namely the environment and control activities over the administration of supplies at Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) of North Sulawesi, which has not been implemented properly, there are still inconsistencies between these two components, namely the frequent occurrence of multiple positions and behavior that lacks integrity and ethics.